2019
DOI: 10.1136/annrheumdis-2019-216266
|View full text |Cite
|
Sign up to set email alerts
|

Response to ‘Titre-specific positive predictive value of anti-nuclear antibody patterns’ by Vulstekeet al

Abstract: Correspondence responsedoes not necessarily hold for the values calculated in the patient cohort from Belgium. Here, we argue that the PPV can even be further increased, as well as the NPV in case of the nuclear dense fine speckled pattern (AC-2), by considering the full ICAP HEp-2 IIFA pattern classification. Eventually, we fully agree with the statement that confirmatory antigen-specific immunoassays are mandatory in all cases, preferentially by taking into account the diagnostic suspicion at the time of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Although most experts suggest using monospecific anti-DFS70 antibodies to exclude SARD [ 2 , 13 , 14 ], we found that in patients presenting with a positive ANA test, using anti-DFS70 antibodies alone without concomitant autoantibody tests could still achieve good specificity [ 38 ]. In apparently healthy individuals, the prevalence of anti-DFS70 antibodies has been reported to be no higher than 30% [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although most experts suggest using monospecific anti-DFS70 antibodies to exclude SARD [ 2 , 13 , 14 ], we found that in patients presenting with a positive ANA test, using anti-DFS70 antibodies alone without concomitant autoantibody tests could still achieve good specificity [ 38 ]. In apparently healthy individuals, the prevalence of anti-DFS70 antibodies has been reported to be no higher than 30% [ 3 ].…”
Section: Discussionmentioning
confidence: 99%